Shop technology - Anderson, James; Tatro, Earl E.; School, Henry Ford Trade ([S.l.] : Macmillan/Mcgraw-Hill School, 2009)
An introductory textbook on machine shop theory and practice, including information on basic machine tools, bench operations, metrology, and career opportunities in the machine trades.